The Effect of Board Size, Leverage, and Company Size on Carbon Emission Disclosure, with Environmental Performance as a Moderation Variable - Puteri, Nasywaa Marshanda Mulyanto; Handayani, Bestari Dwi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
An empirical assessment was carried out to identify key factors influencing the level of carbon emission information disclosed by firms, emphasizing internal governance structure and financial characteristics. The variables examined include board member count, debt utilization, and firm scale, with environmental performance incorporated as a conditional variable. The study concentrates on publicly traded energy companies on the Indonesia Stock Exchange (IDX) over the 2022–2024 timeframe and employs a quantitative research strategy. Data were gathered from publicly accessible annual and sustainability documentation, and the sample was selected based on predefined purposive criteria. The extent of carbon-related disclosure was evaluated using indicators derived from the Carbon Disclosure Project (CDP), while environmental performance was assessed through national PROPER rankings alongside ISO 14001 adoption. To analyze the relationships among variables, panel-based fixed effect estimation and moderated regression techniques were applied. The findings indicate that board size and financial leverage do not serve as significant predictors of carbon emission disclosure practices. In contrast, firm scale exhibits a meaningful positive relationship with disclosure intensity. Additionally, environmental performance does not condition the influence of board size or leverage; however, it interacts with firm scale by reducing its effect on disclosure levels. These results underscore that organizational magnitude plays a central role in determining transparency in carbon emission reporting